Isolation of peat swamp forest foliar endophyte fungi as biofertilizer - Safinah Surya Hakim; Tri Wira Yuwati; Sari Nurulita (Center for Journal Management and Publication, 2017)
Peatland restoration activity is facing many obstacles, particularly in planting techniques and poor nutrient in peat soil. Naturally, endophytic fungi are abundant and have great potential as biofertilizer. This research investigates the potential endophytic fungi isolated from leaves of peat swamp tree species for biofertilizer. Research activities include: exploration, in vitro test to examine the phosphate solubilization and identification. Result showed that there were 360 leave segments collected from 4 sampling locations. The colonization percentage of 222 isolates ranged from 52.17% - 60.17%. Fifty seven morphospecies were selected from 222 isolates. Twelve isolates demonstrated ability to produce clear zones and ten isolates were selected for identification. It is concluded that twelve isolated demonstrated potential ability to produce clear zone and Penicillum citrinum isolate P3.10 was identified as an isolate that show the highest potential ability as a biofertilizer